RANCANG BANGUN E-LEARNING BERBASIS WEB MENGGUNAKAN MOODLE DIINTEGRASIKAN DENGAN TWITTER PADA SMA N 1 SINGOROJO KENDAL (Information Technology and Telematics, 2015)
ABSTRACT Technological developments make better functionality twitter, not only be a social media. Utilization of twitter is be expected to help students SMA N 1 SINGOROJO in teaching and learning process through e-learning system and shared to twitter. This application is created with php programming language and moodle cms for the elearning. Elaerning system beneficial for the learning process bay share a assignment to twitter. this system can make students know a assignment and course from the teacher via twitter. Keywoard: Twitter, e-learning,moodle